HOW MUCH RUGBY IS TOO MUCH? A SEVEN-SEASON PROSPECTIVE COHORT STUDY OF MATCH EXPOSURE IN PROFESSIONAL RUGBY UNION PLAYERS. Issue 4 (1st February 2017) - Williams, Sean; Trewartha, Grant; Kemp, Simon; Brooks, John; Fuller, Colin; Taylor, Aileen; Cross, Matt; Shaddick, Gavin; Stokes, Keith
Abstract : Background: Player welfare concerns have been raised by a number of professional Rugby Union stakeholders regarding the match exposure demands faced by players. Objective: To investigate the influence that acute and chronic match exposures have upon injury risk. Design: A seven-season (2006/7–2012/13) prospective cohort design was used to record time-loss injuries (>24 h) and match exposure. Setting: English Premiership Professional Rugby Union. Participants: 1253 professional players. Assessment of Risk Factors: A player's 12-month match exposure (number of matches a player was involved in for ≥20 mins in the preceding 12 months) and month match exposure (number of full-game equivalent matches in preceding 30 days) were assessed as 'chronic' and 'acute' risk factors, respectively. Main Outcome Measurements: A nested-frailty model was applied to calculate adjusted hazard ratios (HR) for the assessed risk factors. Thresholds for beneficial and harmful effects were 0.90 and 1.11, respectively. Results: 12-month match exposure was associated with injury in a non-linear fashion, with players who had been involved in less than ≈15 or greater than ≈35 matches (for ≥20 mins) over the preceding 12-month period being more susceptible to injury. Monthly match exposure was linearly associated with injury (HR: 1.14 per 2-SD increase, 90% CI: 1.08–1.20; likely harmful), although this effect was substantially attenuated for players in the upper quartile for 12-month match exposure (>28 matches). Conclusions: A player's accumulated and recent match exposure substantially influences their current injury risk. Careful attention should be paid to planning the workload and monitoring the responses of players involved in: 1) a high number of matches in the previous year; 2) a low number of matches in the previous year; 3) a low-moderate number of matches in the previous year but have played intensively in the recent past. These findings could inform match workload planning in professional Rugby Union.